Disordered amorphous calcium carbonate from direct precipitation1. Issue 26 (14th July 2015) - Farhadi Khouzani, Masoud; Chevrier, Daniel M.; Güttlein, Patricia; Hauser, Karin; Zhang, Peng; Hedin, Niklas; Gebauer, Denis
<x xml:space="preserve">Abstract</x> Amorphous calcium carbonate (ACC) precipitated directly from the ion precursors in iso-propanol exhibits no clear proto-structural motifs.